2010
DOI: 10.1177/1077558710384878
|View full text |Cite
|
Sign up to set email alerts
|

Translating Frontiers Into Practice: Taking the Next Steps Toward Improving Hospital Efficiency

Abstract: Frontier techniques, including data envelopment analysis (DEA) and stochastic frontier analysis (SFA), have been used to measure health care provider efficiency in hundreds of published studies. Although these methods have the potential to be useful to decision makers, their utility is limited by both methodological questions concerning their application, as well as some disconnect between the information they provide and the insight sought by decision makers. The articles in this special issue focus on the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
0
14
0
3
Order By: Relevance
“…Thereby, in the efficiency analysis literature there has been considerable interest in reconciling SFA and DEA [6]. Two studies that compared SFA and DEA are Chirikos and Sear [7] for US hospitals and Jacobs [2] for hospitals in the UK where both studies found divergent estimations between the results from the two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, in the efficiency analysis literature there has been considerable interest in reconciling SFA and DEA [6]. Two studies that compared SFA and DEA are Chirikos and Sear [7] for US hospitals and Jacobs [2] for hospitals in the UK where both studies found divergent estimations between the results from the two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of clinical outcome measures, patient satisfaction is often used as a proxy for both care quality and operational effectivenessVin addition to being an important measure in its own right (Salinas-Jiménez & Smith, 1996). Furthermore, empirical work has shown a positive relationship between hospital efficiency and performance measures (Mutter, Rosko, Greene, & Wilson, 2011;Nayar, Ozcan, Yu, & Nguyen, 2013;. However, it is unclear if managers have the wherewithal to influence care processes that link patient satisfaction and efficiency vis-(-vis other direct care professionals.…”
mentioning
confidence: 99%
“…Sherman () provides an early application to hospital productivity and Mutter et al . (), a recent example, but there have been applications to physician practices as well (Andes et al ., ).…”
Section: Data Envelopment Analysismentioning
confidence: 99%